Sjukdom i ord och bild. Inferno av August Strindberg och August Strindbergs Inferno av Fabian Göranson - Żmuda-Trzebiatowska, Magdalena (Folia Scandinavica Posnaniensia, 2024)
Inferno (1897) is one of the most significant works in August Strindberg’s vast oeuvre. It has been subject to many interpretations but due to its multidimensionality it defies clear classification and therefore continues to arouse the interest of researchers. In many respects it can be considered as an illness narrative because the autobiographical story of August Strindberg who suspends his writing career and gives up his family life to dedicate himself to science is indeed to a great extent a retrospective study of a deep mental crisis or even a schizophrenic episode. The hero suffers from delusions of grandeur and a persecution complex, succumbs to hallucinations and becomes entangled in religious and philosophical speculations desperately seeking a way out of his spiritual hell. Strindberg’s work inspired Swedish illustrator Fabian Göranson who published his graphic novel August Strindbergs Inferno in 2010. The aim of the article is to look at, using selected examples, descriptions of physical and spiritual torments in Strindberg’s text and compare them with the corresponding scenes created by Göranson by means of images and words.